STRATEGI PEMBIAYAAN PENDIDIKAN DAN PENGALOKASIAN BIAYA PENDIDIKAN DI SDN KALIREJO 01 - Jaya Yanti Nur Istiqomah; Kurnia Permata Nur Aisah; Dyah Ayu Permatasari; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study conducted an in-depth examination of the educational financing conditions at SD Negeri Kalirejo during the 2024/2025 academic year. The qualitative analysis revealed that although the School Operational Assistance (BOS) fund is the primary source of funding, there are several significant challenges that hinder the optimal utilization of these funds. Limited allocated budgets, regulations restricting additional funding sources, and a relatively small number of students have impacted the quality of education services that the school can provide. This situation demands creative and innovative efforts to find long-term solutions to address the educational financing challenges faced by the school.